Electromagnetic processes at high energies in oriented single crystals - Baier, V. N. (World Scientific, 1998)
This book is devoted to processes in the interaction of high-energy charged particles and photons with crystals, including creation of electron-positron pairs by photons in a crystalline field and the radiation of particles in this field. Connected with these effects are new types of electromagnetic showers in crystals; channelling of fast particles in crystal; and channelling radiation. At high energy the processes of quantum electrodynamics (QED) in intense external fields play an important role in crystals. The first one-third of the book contains the new formulation of QED in external fields, which is valid for any external field, including essentially non-uniform ones and has vast applications.